Recovery of Forearm and Fine Digit Function After Chronic Spinal Cord Injury by Simultaneous Blockade of Inhibitory Matrix Chondroitin Sulfate Proteoglycan Production and the Receptor PTPσ - Milton, Adrianna J; Kwok, Jessica C F; McClellan, Jacob; Randall, Sabre G; Lathia, Justin D; Warren, Philippa M; Silver, Daniel J; Silver, Jerry (Journal of neurotrauma, 2023)
Spinal cord injuries (SCI), for which there are limited effective treatments, result in enduring paralysis and hypoesthesia, in part because of the inhibitory microenvironment that develops and limits regeneration/sprouting, especially during chronic stages. Recently, we discovered that targeted enzymatic removal of the inhibitory chondroitin sulfate proteoglycan (CSPG) component of the extracellular and perineuronal net (PNN) matrix via Chondroitinase ABC (ChABC) rapidly restored robust respiratory function to the previously paralyzed hemi-diaphragm after remarkably long times post-injury (up to 1.5 years) following a cervical level 2 lateral hemi-transection. Importantly, ChABC treatment at cervical level 4 in this chronic model also elicited improvements in gross upper arm function. In the present study, we focused on arm and hand function, seeking to highlight and optimize crude as well as fine motor control of the forearm and digits at lengthy chronic stages post-injury. However, instead of using ChABC, we utilized a novel and more clinically relevant systemic combinatorial treatment strategy designed to simultaneously reduce and overcome inhibitory CSPGs. Following a 3-month upper cervical spinal hemi-lesion using adult female Sprague Dawley rats, we show that the combined treatment had a profound effect on functional recovery of the chronically paralyzed forelimb and paw, as well as on precision movements of the digits. The regenerative and immune system related events that we describe deepen our basic understanding of the crucial role of CSPG-mediated inhibition via the PTPσ receptor in constraining functional synaptic plasticity at lengthy time points following SCI, hopefully leading to clinically relevant translational benefits.
Keywords: Animals; Female; Spinal Cord; ženské pohlaví; chondroitinsulfát proteoglykany; Chondroitin Sulfate Proteoglycans; Chondroitin ABC Lyase; receptor PTPσ; chondroitinasa ABC; mícha; poranění míchy; Receptor-Like Protein Tyrosine Phosphatases, Class 2; CSPGs; axon sprouting; Rats, Sprague-Dawley; regenerace nervu; perineuronal net; Nerve Regeneration; Spinal Cord Injuries; spinal cord injury; potkani Sprague-Dawley; tyrosinfosfatasy receptorového typu, třída 2; axon regeneration; krysa rodu Rattus; zvířata; Rats; přední končetina; Forelimb